Brain activity during concentric and eccentric muscle contractions of the biceps brachii - Lee, Glen Wai Chong (2019)
Literature has provided evidence of distinct cortical activation patterns between eccentric and concentric movement. But, the exact mechanism and motor network in the brain that controls eccentric and concentric movement remains limited. There is conflicting evidence regarding the activation pattern in the primary motor cortex (M1) during eccentric and concentric exercise. This study’s purpose is to examine the activation of the contralateral and ipsilateral M1 during each mode of muscle contraction (eccentric and concentric) and at various loading intensities. Ten participants aged between 21 to 35 years old were recruited for a randomized crossover study. Three laboratory sessions were conducted. In the first session, participants recorded their eccentric and concentric maximal voluntary contraction (MVC). For each of the second and third session, participants performed three sets of four repetitions at 20% MVC and again at 80% MVC. The type of muscle contraction and the order of contraction intensity performed in each session was randomly allocated. The contractions were performed on an isokinetic dynamometer and M1 activation was recorded using a near infrared spectroscopy system. There were no significant differences in contraction mode (p = 0.440) and contraction intensity (p = 0.416) respectively on M1 activation. The findings indicated that the M1 does not mediate eccentric and concentric contraction as well as 20% and 80% MVC intensities differently. Future studies can examine potential interactions and coupling effects between the M1 and other cortical regions as well as explore the cortical activation that may occur in other neural areas.